EMTSN criterion for evaluating mixed mode I/II crack propagation in rock materials. (1st March 2018) - Mirsayar, M.M.; Razmi, A.; Aliha, M.R.M.; Berto, F.
Graphical abstract: Highlights: Studies mixed mode I/II brittle fracture behavior in rock materials. Examines two sets of fracture test data from two different specimens. Traditional fracture criteria cannot predict test data properly. EMTSN criterion predicts fracture angles and fracture toughness very well. Abstract: This paper investigates the results of brittle fracture in rock materials subjected to the mixed mode I/II loading using different fracture criteria. Two sets of mixed mode fracture test data in the entire range of mode mixity, from pure mode I to pure mode II, reported in the literature for semi-circular and triangular shape specimens and subjected to three point bend loading (i.e. SCB and ECT specimens) are utilized to study the brittle fracture in two marble rocks. First, the onset of fracture initiation is examined by different conventional fracture criteria including Maximum Tangential Stress (MTS) and Maximum Tangential Strain (MTSN) criteria. It is shown that these two conventional fracture criteria, which only consider singular crack tip stress/strain terms, are not able to accurately predict the mixed mode fracture test data. The experimental mixed mode fracture toughness data are then predicted by an extended version of the maximum tangential strain (EMTSN) criterion which takes into account the effect of first nonsingular strain term as well as the singular strain components. It is found that both mixed mode fracture toughness results of the investigated rock materials and the crack propagation direction can be predicted successfully by the EMTSN criterion.